Boost photothermal theranostics via self‐assembly‐induced crystallization (SAIC). Issue 5 (26th January 2022) - Mu, Xueluer; Wu, Fapu; Tang, Ying; Wang, Rui; Li, Yajie; Li, Kaixuan; Li, Chunfeng; Lu, Yingxi; Zhou, Xianfeng; Li, Zhibo
Abstract: Owing to the intrinsic advantages of spatiotemporal selectivity, photothermal theranostics have become the advancing edge of precision medicine for cancer. Developing photothermal transduction agents (PTAs) with near‐infrared (NIR) absorption, high photothermal conversion efficiency, robust photothermal stability, and good accumulation in tumors, is particularly valuable. Herein, we report a new concept, self‐assembly‐induced crystallization (SAIC), which can serve as a mechanism that dramatically boosts photothermal behaviors of PTA in NIR region. As a proof of concept, three heptamethine cyanine molecules with internal degrees of freedom (geometry and intramolecular interaction) are designed to fine‐tune their crystallinity. Notably, Cy7‐TCF‐EMBI molecules with rigid and planar skeletons self‐assemble into a crystalline state to maximize their packing density and improve the charge transfer, both of which contribute to nonradiative decay for energy dissipation as heat. The high packing density also renders an ideal scaffold for controlling intermolecular interactions to exhibit better photothermal stability, and endows an anisotropic three‐dimensional architecture for passive tumor targeting. This "SAIC" strategy may offer a conceptually novel, practically simple but effective approach to unveil the structure–property relationship that could provide some general rules in rational design of PTAs, and paves the way for a next generation of supramolecular medicine for photothermal theranostics. Abstract : We report a new concept, self‐assembly‐induced crystallization (SAIC), which can be served as a mechanism to dramatically boost photothermal theranostic properties of small‐molecule in NIR region. This supramolecular strategy of "SAIC" may offer an approach to unveil structure–property relationships in rational design of small‐molecule photothermal theranostic agents, and paves the way for next generation of supramolecular medicine for photothermal theranostic.